## Find out the missing digit – 30 43 51 ?

Number Puzzle #175

find out the missing number

2 3 1 2

3 4 4 5

5 6 6 7

30 43 51 ?

## IF 5 7 3 20 10 30 then 95 45 ?

## Missing number Puzzle X 21 147

## Number Puzzle #173

2 6 18

4 20 100

X 21 147

find X

Check your answer:-

**Answer**: X = 3

**Solution**

in first row next number is a multiplication of 3 and the previous number

second row, next number is a multiplication of 5 and the previous number

in third row 3rd number (147) is a multiplication of 7 and previous number, i.e. 21, thus X*7 = 21 =>

**x = 21/7 = 3**

## Number Puzzle #172

### Let’s see who can crack this:-

If 10-2= 33

37-23=83

82-4= 43

55-7=32

then 76-45=?

## IF 1=2, 2 = 10, 3 = 30, 4=68 Then 5 =?

## Number Puzzle #171

Find out the numbers in the boxes

A | + | B | = | 8 |

+ | + | |||

C | – | D | = | 6 |

|| | || | |||

13 | 8 |

Check your answer:-

Top Left Box

Bottom Left Box

Bottom Right Box

Answer With Explanation

**Answer**:

3.5 | + | 4.5 | = | 8 |

+ | + | |||

9.5 | – | 3.5 | = | 6 |

|| | || | |||

13 | 8 |

**Explanation**:

We can make four equations

A+B = 8

C-D = 6

A+C = 13

B+D = 8

now we have four variables with four equations so it should be easy to solve. let’s solve these four equations

if we add the four equations

A+B+C-D+A+C+B+D = 8 + 6 + 13 + 8

2(A+B) + 2C = 35

2C = 35 – 2*8 —- by replacing A+B

2C = 35 – 16 = 19

C = 9.5

from 2nd Equation C – D = 6

D = C – 6

D = 9.5 – 6

D = 3.5

from 3rd equation

A+C = 13

A = 13 – C

A = 13 – 9.5

A = 3.5

from 4th equation

B + D = 8

B = 8 – D

B = 8 – 3.5

B = 4.5

## If February=June what is March?

## Number Puzzle #170

If February=June,

January=April,

September=September,

and August=April…

then **what is March?**

## Number Puzzle (This is NOT an easy one)

## Number Puzzle #169

IF,

9 = 100,

8 = 143,

7 = 162,

6 = 165,

Then,

5 = ?

## Number Puzzle #168 – If 1 + 2 = 13 Then

# Number Puzzle #168

If 1 + 2 = 13

2 + 3 = 61

3 + 4 = 193

Then 4 +5 = ?

Check your answer:-

**Answer**: 481

**Explanation**:

A+B = (A*B + 2)^2 – 3

Answered by: in disqus comments.

- « Previous Page
- 1
- 2
- 3
- 4
- 5
- …
- 22
- Next Page »